Springtime phytoplankton responses to light and iron availability along the western Antarctic Peninsula. Issue 4 (16th February 2022) - Joy‐Warren, Hannah L.; Alderkamp, Anne‐Carlijn; van Dijken, Gert L.; J. Jabre, Loay; Bertrand, Erin M.; Baldonado, Evan N.; Glickman, Molly W.; Lewis, Kate M.; Middag, Rob; Seyitmuhammedov, Kyyas; Lowry, Kate E.; van de Poll, Willem; et al.
Abstract: Light and iron availability are intertwined in controlling Southern Ocean primary production because several photosynthetic proteins require iron. Changes in light and iron availability can also affect phytoplankton species composition, which impacts nutrient cycling, carbon drawdown, and food web structure. To investigate the interactive effects of light and iron on phytoplankton growth, photosynthesis, photoacclimation strategy, micronutrient stress‐induced protein expression, and species composition, we conducted five bioassay experiments during spring in waters along the western Antarctic Peninsula with four treatments: low light (LL) or high light (HL) combined with or without iron addition. This region has rarely been studied in spring. We found that light limits growth while iron does not, despite overall low iron concentrations. Our results demonstrate that phytoplankton were LL acclimated in situ but photosynthetically optimized for higher light than they were experiencing, likely due to a highly dynamic light regime. Expression patterns of micronutrient stress‐induced proteins were consistent with iron stress in off‐shelf regions, but remarkably this iron stress did not result in lower carbon fixation and growth rates. Notably, manganese drawdown was highest under elevated light, suggesting a possible role in managing HL, although high flavodoxin expression indicated that Phaeocystis antarctica may not have been manganese‐limited. Although light and iron treatments did not impact species composition, high methionine synthase indicated that diatoms could have experienced stress induced by low vitamin B12, potentially contributing to P. antarctica 's general dominance throughout the experiments. Our results indicate that P. antarctica may be better adapted to spring conditions than diatoms.